Optimization of the Extraction Process for 6-Gingerol-Rich Extract from Zingiber officinale Roscoe Residue Using the Response Surface Methodology - Tu, Nguyen Thi Minh; Thao, Nguyen Thi; Son, Vu Hong; Minh, Pham Anh; Hiep, Nguyen Tuan (International Journal of Research in Interdisciplinary Studies, 2025)
Optimizing the extraction of 6-gingerol enriched extract from ginger’s (Zingiber officinale Roscoe) residue after distillation is essential for enhancement the value of ginger by-products. Typically, ginger residue is either discarded or underutilized, resulting in resource wastage and environmental concerns. Given the significant pharmacological and economic potential of 6-gingerol, a main compound, an efficient extraction process can enhance sustainability, minimize waste, and support the development of ginger exploitation. This study aims to improve resource efficiency and promote a circular economy in ginger processing by refining the extraction process for higher yield and effectiveness.